EVALUATION OF THE PROTECTIVE EFFECT OF SILYMARIN ON DOXORUBICIN INDUCED CHRONIC TESTICULAR TOXICITY IN RATS - VIJAY KRANTI.M; MAHESH.V; SRINIVAS.P; Y.V.GANESH; AJAY GODWIN.P; DR. MANGALA LAHKAR (International Journal of Pharma and Bio Sciences, 2013)
Doxorubicin (DOX) (also known as hydroxyl daunorubicin or Adriamycin) is a cytotoxic, anthracycline antibiotic drug isolated from the soil fungus Streptomyces peucetius caesius. DOX is widely used as intravenous antimitotic neoplastic to treat wide range of solid tumours. It has been shown to produce reproductive abnormalities in males. Silymarin (SYL), a flavanolignan compound extracted from seeds of ‘milk thistle’ (Silybum marianum), is an antioxidant well known for its hepatoprotective action. The present study was aimed to evaluate the protective effect of SYL on DOX induced testicular toxicity in rats. SYL was administered at a dose of 100mg/kg, 200mg/kg, and 300mg/kg to rats which are simultaneously given DOX (3mg/kg) to induce testicular toxicity. The treatment was given for a period of 5 weeks. SYL treatment maintained near normal levels of sperm count, testicular spermatid head concentration, daily sperm production, Serum testosterone levels and normal spermatogenesis when compared to positive control.